Odpowiedź :
Dzielenie ulamka przez ulamek to mnozenie ulamka przez odwrotnosc drugiego ulamka.
[tex]5\frac12:3\frac23=\frac{11}2:\frac{11}3=\frac{11}2*\frac3{11}=\frac32\\\\3\frac23:2\frac34=\frac{11}3:\frac{11}4=\frac{11}3*\frac4{11}=\frac43=1\frac13\\\\\frac59:\frac13=\frac59*3=\frac53=1\frac23\\\\2\frac79:\frac56=\frac{25}9*\frac65=\frac53*2=\frac{10}3=3\frac13\\\\\frac34:1\frac78=\frac34:\frac{15}8=\frac34*\frac8{15}=\frac11*\frac25=\frac25\\\\2\frac56:2\frac34=\frac{17}6:\frac{11}4=\frac{17}6*\frac4{11}=\frac{17}3*\frac2{11}=\frac{34}{33}=1\frac1{33}\\\\[/tex]
[tex]4\frac23:1\frac26=\frac{14}3:\frac86=\frac{14}3*\frac68=\frac{7}{1}*\frac{2}{4}=\frac{14}4=\frac72=3\frac12[/tex]
[tex]10:\frac22=10:1=10[/tex]
Odpowiedź:
5 i 1/2 : 3 i 2/3= 11/2 : 11/3= 11/2 *3/11 ( skracamy 11 i 11 przez 11)=1/2*3=
= 3/2= 1 i 1/2
3 i 2/3 : 2 i 3/4= 11/3 : 11/4= 11/3 *4/11 ( skracamy 11 i 11 przez 11)=
=1/3 *4= 4/3= 1 i 1/3
5/9 : 1/3= 5/9 *3= 15/9= 1 i 6/9= 1 i 2/3
2 i 7/9 : 5/6= 25/9 : 5/6= 25/9 * 6/5( skracamy 25 i 5 przez 5, oraz 9 i 6
przez 3)= 5/3 *2= 10/3= 3 i 1/3
3/4 : 1 i 7/8= 3/4 ; 15/8= 3/4 * 8/15 ( skracamy 15 i 3 przez 3, oraz 4 i 8
przez 4)= 2/5
2 i 5/6 : 2 i 3/4= 17/6 ; 11/4= 17/6 *4/11 ( skracamy 4 i 6 przez 2)=
=17/3 *2/11= 34/33= 1 i 1/33
4 i 2/3 : 1 i 2/6= 14/3 : 8/6= 14/3 *6/8( skracamy 3 i 6 przez 3 , oraz
14 i 8 przez 2)=7*2/4= 14/4= 3 i 2/4
10 : 2/2= 10:1= 10
Szczegółowe wyjaśnienie: